Identifikasi kualitas proses shield metal arc welding (SMAW) melalui monitoring arus dan daya real-time - A. Sifa; T. Endramawan; N. Niantoro (Dinamika Teknik Mesin, 2020)
The shield metal arc welding Monitoring welding process is simple and more economical so it is widely used in small and large industries, and can also be used anywhere, quality control is very important to ensure the results of welding connections have good quality, some important parameters in the welding process include current, voltage and welding speed. Monitoring of the welding process is very important in addition to monitoring the quality of the process and the results of welding; the monitoring process is very effective and efficient without the need for additional time and costs to carry out damaged tests after the welding process. Real-time monitoring method using the Arduino microcontroller system, the welding experiment process is carried out at position 1F with two sides and using ST37 steel material and after welding the quality is checked using the method Non-Destructive Test-Liquid Penetration Test. The result of in the welding process the minimum current occurs is 21 amperes occurs in the welding process position 1F and the maximum current that occurs is 41.1 defects occur when the current is below 27.5 Amperes, in addition to the current that causes the welding defects, other variables can also cause welding defects such as welding position 1F part B there are defects in the welding process with 29 Amperes Flow, and identification of welding quality through a real-time monitoring system with current and power parameters.